الأمن البشري العربي الواقع والآفاق - الناصر, منذر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن تحقيق الأمن الاقتصادي والغذائي هو محرك كل تطور وتقدم للإنسان العربي كي يتمكن من التفاعل والتجاوب مع المتغيرات العالمية المتسارعة بكفاءة واقتدار. سنحاول من خلال هذه الدراسة توضيح أهمية الأمن البشري العربي وتحديد مكوناته الأساسية, خاصّةً في ظروف العولمة وتأثر الأمن البشري العربي بسلبياتها التي يمكن أن تظهر من خلال انتشار المرض والجوع والبطالة, حيث تؤثر هذه النتائج كافة على عدم وصول الناس إلى فرصهم الاجتماعية والاقتصادية. ويتضمن البحث المحاور الآتية: - المحور الاول: يبحث في مفهوم الأمن البشري، والتنمية البشرية. - المحور الثاني: المحددات الأساسية للأمن البشري، وسنتعرض فقط للمحددات التالية (الأمن الاقتصادي، الأمن الغذائي). - المحور الثالث: يظهر آفاق الأمن البشري العربي وأهمية التكامل الاقتصادي العربي في تحقيق الأمن البشري. This research handles the relation between the variables of international and some factors of Arabian human security, especially: economic security, the alimentary security. These factors are forming the types of most important of human security. Truly, achievement the economic security and the alimentary security is dynamo all development and progress for Arabian human so that to have the interaction and reaction ability along with hurrying variables of international by efficiency and worthy. We will try through this research, illustration, the importance of Arabian human security. In addition, definition its major compositions, especially: in circumstances of the globalizing, moreover, touch the Arabian human security by its negative. The Research contains the following items. First item: search in human security form, and human development Second item: search in major factors for human security, we will showing the following factors (the economic security, the alimentary security). Third item: show the importance of Arabian economic integration to achieve the human security.